Development of a warning system for wheat blast caused by Pyricularia grisea - Cardoso,Cinara Araújo de Andrade (2008)
Wheat (Triticum aestivum L.) blast caused by Pyricularia grisea is a new disease in Brazil and no resistant cultivars are available. The interactions between temperature and wetness durations have been used in many early warning systems. Hence, growth chamber experiments to assess the effect of different temperatures (10, 15, 20, 25, 30 and 35ºC) and the duration of spike-wetness (0, 5, 10, 15, 20, 25, 30, 35 and 40 hours) on the intensity of blast in cultivar BR23 were carried out. Each temperature formed an experiment and the duration of wetness the treatments. The highest blast intensity was observed at 30°C and increased as the duration of the wetting period increased while the lowest occurred at 25°C and 10 hours of spike wetness. Regardless of the temperature, no symptoms occurred when the wetting period was less than 10 hours but at 25°C and a 40 h wetting period blast intensity exceeded 85%. These variations in blast intensity as a function of temperature are explained by a generalized beta model and as a function of the duration of spike wetness by the Gompertz model. Disease intensity was modeled as a function of both temperature and the durations of spike wetness and the resulting equation provided a precise description of the response of P. grisea to temperatures and the durations of spike wetness. This model was used to construct tables that can be used to predict the intensity of P. grisea wheat blast based on the temperatures and the durations of wheat spike wetness obtained in the field.